Postscript: Feminist Legal Theory in the 21st Century - Margaret Thornton (Laws, 2020)
This editorial takes the form of a short postscript to a special issue of Laws published in 2019–20. It shows how feminist legal theory (FLT), a corollary of second wave feminism, was initially embraced by law schools but soon subjected to a backlash. FLT was nevertheless able to turn around the negative discourse of post-feminism to show that the “post” can mean not just the end but a new beginning. The Special Issue attests to the resurgence of FLT in the 21st century.